The welfare effects of trade liberalization : evidence from the car industry in Colombia (2004)
In this paper I examine the effects of trade liberalization on firms' performance and consumers' welfare. Using product level data, I study firms' performance in the Colombian automobile industry. Given my disaggregated data I can estimate pre and post-reform pricecost margins, as well as calculate the results by origin of production. Before the reforms were implemented, imported cars had prohibitively high tariffs, on average 200%, and were essentially unavailable. After the reforms such tariffs were reduced to 38% on average. I find that as the industry restructured prior to the liberalization process, price-cost margins dropped from 33% to 24%. After the reforms, margins increased because of the associated lower costs, but then again started to fall, reaching a low 23% for domestic cars. The behavior of price-cost margins is explained by increasing domestic competition prior to the reforms, the associated decrease in costs after the reforms and the relatively unchanged market structure. On the consumer side, the approach I follow allows me to estimate the monetary gains due to the liberalization process. I find the post-reform gains in consumers' welfare to be, as a consequence of declining prices and increased variety, over three thousand dollars per purchaser. A counterfactual simulation, where it is assumed that no foreign cars were available after the reforms, suggests that the gains achieved by consumers are due, for the most part, to increased variety rather than to price competition.